Heroic representation in the citations of Medal of Honor recipients / Samini Anmpalagan - Samini , Anmpalagan (2018)
This study examines the way soldiers as social actors are represented as heroes in the citations of the Medal of Honor. The objectives are to discover how soldiers are represented as heroes (the textual strategies of hero constructions) as well as to uncover the underlying ideological positioning that is reflected through the citations. This is done through the analysis of the textual strategies used in the said citations using Van Leeuwen‟s Social Representation Theory. Using this framework, 40 citations from the official website at www.cmohs.org are selected and examined. The findings show the use of activation, individualisation, nomination and functionalization as a mean to represent and project the recipients as heroes. From the findings, it is believed that the voice of the decision makers is incorporated by inserting ideological representation into the discourse.